Implementation of Software For Efficient Inventory Management at A National Peruvian University - Velasquez-Jimenez, Linett; Marrujo-Ingunza, Claudia; Rubiños-Jimenez, Santiago; Grados-Gamarra, Juan; Grados-Espinoza, Junior (Journal of Applied Engineering and Technological Science (JAETS), 2025)
This study presents the design and implementation of a multiplatform inventory management system developed for a public university in Peru, aiming to improve process efficiency and user satisfaction. Following an agile development methodology (SCRUM), the system was designed using modular architecture and responsive interfaces to ensure compatibility across devices and browsers. The usability evaluation was carried out using the CSUQ questionnaire, and the results were transformed to the SUS scale to assess the overall experience. A descriptive quantitative methodology was used, supported by surveys and technical compatibility testing. The findings reveal high user satisfaction, a SUS score of 93.75 ("Best imaginable"), and strong performance across all functionalities, particularly in navigation and inventory tracking. These results confirm the effectiveness of agile development in higher education contexts and highlight the importance of user-centered design in administrative systems.